Canaries: Management, nutrition, common disorders - IORDANIDIS (Π. ΙΟΡΔΑΝΙΔΗΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
Commercial production of canaries, which are among the most popular birds worldwide, is based mainly on the nice singing, good-looking feather coloration and total appearance of these birds. Population of canaries in Greece is bigger in comparison with other birds (psittacines, etc.). These birds live separately in cages or in groups in production units. The number of birds, which are being carried to private surgeries, is continuously increasing. Despite some difficulties, such as small size, great sensitivity, susceptibility to stress, and inconvenience in administrating drugs in accurate doses, a veterinarian may proceed to therapies or even operations in canaries with good results. Principals of canaries’ management and nutrition, as well as the most commonly encountered cases are described in the present paper. Such cases include stop of singing, feather problems and severe lisdessness. Brief description of the problems mentioned above and the methods of control may offer to the practitioner the knowledge to approach such cases in his surgery.